ANALYSIS OF BIOLOGY EDUCATION STUDENTS' KNOWLEDGE LEVEL ON THE TOPIC OF BIOPRENEURSHIP - Rangkuty, Sailana Mira; Amrizal, Amrizal; Mukra, Rizal; Rahmawati, Suci (Universitas Negeri Medan, 2024)
The aim of this research is to determine the level of knowledge of biology education students on the topic of Biopreneurship. This research uses a descriptive evaluative method, namely a study method that evaluates objective conditions or what they are in a situation that is the object of study. The analysis used is descriptive qualitative, namely research that accurately describes the nature of an individual, certain circumstances or symptoms so that they can be described thoroughly. Data collection was carried out using several techniques, namely literature studies and field observations. Biontrepreneurship is the integration of biological sciences with business sciences which involves all aspects of living things. Biopreneurship is defined as the use of living things that can be processed into business products and can be marketed, resulting in a productive economy. Seeing the importance of Biopreneurship, interdisciplinary learning began to be carried out. This is done so that students are able to combine their knowledge to apply it to solve various problems in the real world. The results of the analysis show that biology education students' knowledge on the topic of Biopreneurship is in the high category with a score of 82. Based on the level of Biopreneurship knowledge which is categorized as high, it is estimated that students will be able to design good Biopreneurship products.